Constitutional guarantees generate negative externalities for the brazilian health system - Sandra Mara Campos Alves; Alethele de Oliveira Santos; Ivan Pricken Bem; Talita Rodrigues Gomes; Maria Célia Delduque (Oswaldo Cruz Foundation, Health Law Program, 2016)
The research was conducted in 27 Brazilian courts of law. We aimed to know the legal demands on health and the arguments made by the patient, the defense, and the judge in judicial hearings. For this, we used the method of case law research. The research unit was Brazilian judicial processes with the material object of health demands, decided between 2012 and 2013.The results showed reliance on constitutional arguments for both the request and the decision, while the defense was based on diverse and obsolete legal points. It was concluded that judges have decided questions about health using purely legal arguments and reproducing points made by the patient. The defense of the Brazilian health system is fragile due to the lack of an adequate legal rationale.